Factors Influencing User’s Continuance Usage Willingness Of E-learning In China - Jin, Kai (2024)
E-Learning has become a new way for people to receive an education. Nowadays, the scale of E-Learning is growing rapidly, and the Chinese Business-to-Consumer (B2C) market of the E-Learning industry is promising and has become a new industry of general concern. However, the homogenization problems of products, the low willingness of newly registered users rate, and low retention became prominent. How users use E-Learning apps may yield important theoretical and practical implications for scholars and companies. Thus, considering the Technology Continuance Theory (TCT) model, task technology fit (TTF) model, and with extra new variables, this study examined the determinants impacting the user’ E-Learning Continuance Usage Willingness (CUW) in China. This study examined the relationship between Satisfaction, Attitude, Trust, Privacy, Security, Perceived Ease of Use (PEOU), Information Quality, Service Quality, TTF, technology characteristics (TEC), task characteristics (TAC), Course Trial, Perceived Cost, Perceived Usefulness (PU), and E-Learning Continuance Usage Willingness in the Chinese E-Learning market. It also examined the moderating effect of Experience in B2C platform. The positivist paradigm is adopted for this study. Realism is chosen for ontology, and empiricism is chosen for epistemology. A survey research methodology was adopted in this study, and the questionnaires was distributed to E-Learning users in China.